Combined, short-term exposure to reduced seawater pH and elevated temperature induces community shifts in an intertidal meiobenthic assemblage. (February 2018) - Mevenkamp, Lisa; Ong, Ee Zin; Van Colen, Carl; Vanreusel, Ann; Guilini, Katja
Abstract: In future global change scenarios the surface ocean will experience continuous acidification and rising temperatures. While effects of both stressors on marine, benthic communities are fairly well studied, consequences of the interaction of both factors remain largely unknown. We performed a short-term microcosm experiment exposing a soft-bottom community from an intertidal flat in the Westerscheldt estuary to two levels of seawater pH (ambient pHT = 7.9, reduced pHT = 7.5) and temperature (10 °C ambient and 13 °C elevated temperature) in a crossed design. After 8 weeks, meiobenthic community structure and nematode staining ratios, as a proxy for mortality, were compared between treatments and structural changes were related to the prevailing abiotic conditions in the respective treatments (pore water pHT, sediment grain size, total organic matter content, total organic carbon and nitrogen content, phytopigment concentrations and carbonate concentration). Pore water pHT profiles were significantly altered by pH and temperature manipulations and the combination of elevated temperature and reduced pH intensified the already more acidic porewater below the oxic zone. Meiofauna community composition was significantly affected by the combination of reduced pH and elevated temperature resulting in increased densities of predatory Platyhelminthes, reduced densities of Copepoda and Nauplii and complete absence of Gastrotricha compared to the experimental control. Furthermore, nematode staining ratio was elevated when seawater pH was reduced pointing towards reduced degradation rates of dead nematode bodies. The observed synergistic interactions of pH and temperature on meiobenthic communities and abiotic sediment characteristics underline the importance of multistressor experiments when addressing impacts of global change on the marine environment. Highlights: Seawater acidification and warming induced shifts in a meiobenthic community. Effects of both stressors on pore water pH were synergistic. Meiobenthic groups showed divergent density responses to both stressors. Less abundant groups responded more pronounced, nematode densities remained similar.